Are my religious beliefs anyone’s business? A framework for declarations in health and biomedicine - Ghinea, Narcyz (Journal of medical ethics, 2021)
Conflicts of interests (COI) are typically divided into those that are financial and those that are not. While there is general agreement that financial COIs have a significant impact on decisions and need to be declared and managed, the status of non-financial COIs continues to be disputed. In a recent BMJ feature article it was proposed that religious beliefs should be routinely declared as an interest. The article generated over 41 responses from the medical community and health researchers, which put forward diverse and opposing views. In this paper, we analyse the discourse to shed further light on the reasons put forward for and against declaring religious beliefs. We argue for a middle path in which only material beliefs should be declared, and then only when there are no extenuating circumstances. To this end, we present a framework to help evaluate the materiality of interests that can be used for both financial and non-financial interests.Data are available in a public, open access repository.